2011
DOI: 10.1111/j.1365-2966.2011.20058.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of rising magnetized cavities and ultrahigh energy cosmic ray acceleration in clusters of galaxies

Abstract: We study the expansion of low‐density cavities produced by active galactic nucleus jets in clusters of galaxies. The long‐term stability of these cavities requires the presence of linked magnetic fields. We find solutions describing the self‐similar expansion of structures containing large‐scale electromagnetic fields. Unlike the force‐free spheromak‐like configurations, these solutions have no surface currents and, thus, are less susceptible to resistive decay. The cavities are internally confined by external… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…It is important to emphasize that our finding regarding the plasma β parameter being of the order of unity in the giant lobes of Centaurus A may be crucial for understanding the dynamics and evolution of the reconnecting magnetic field in the system. Gourgouliatos & Lyutikov (2012) argued for example that the evolution of the expanding lobes containing some thermal plasma and some magnetic flux will always be accompanied by a decrease in the β parameter, leading at some point to the spontaneous formation of electric current sheets and large-scale reconnection layers which are likely involved in acceleration of the highest energy cosmic rays.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that our finding regarding the plasma β parameter being of the order of unity in the giant lobes of Centaurus A may be crucial for understanding the dynamics and evolution of the reconnecting magnetic field in the system. Gourgouliatos & Lyutikov (2012) argued for example that the evolution of the expanding lobes containing some thermal plasma and some magnetic flux will always be accompanied by a decrease in the β parameter, leading at some point to the spontaneous formation of electric current sheets and large-scale reconnection layers which are likely involved in acceleration of the highest energy cosmic rays.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have suggested that self-organized, nearly force-free fields exist within radio lobes and cavities (e.g. [30,48]). These structures are the end point of magnetic (or Taylor) relaxation, which develops spontaneously if magnetic energy and helicity are injected into the system (e.g.…”
Section: From Theory: Inhomogeneous Modelsmentioning
confidence: 99%
“…A further important effect of the injected magnetic field will be to stabilize the bubble surfaces against fluid instabilities (e.g. Gourgouliatos & Lyutikov 2012).…”
Section: Implications Of Expelled Frozen-in Magnetic Fieldmentioning
confidence: 99%